Renewable Energy: Concept, Technology and Uses - Okeke, O. C.; Onukuba, D. Ken; Enwelu, C. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2016)
This paper looks into the various sources of renewable energy which includes solar, wind, geothermal, hydroelectric and biomass. Renewable energy supplies encompass a broad range of resources, and numerous technologies can be used to tap these resources. Some of these technologies include photovoltaic: solar hot water and solar thermal electric for solar energy technologies; the turbine technologies for wind energy; dry steam, flash steam, and binary cycle power plants for geothermal energy; and biochemical, thermo chemical, pyrolysis processes for biomass. The benefits associated with these energy technologies were also explored. These benefits include improved public health and environmental quality, power generation, jobs and other economic benefits; and stabilization ofenergy price.